Fast protocol for the processing of split-thickness skin into decellularized human dermal matrix. (October 2021) - Pérez, M.L.; Castells-Sala, C.; López-Chicón, P.; Nieto-Nicolau, N.; Aiti, A.; Fariñas, O.; Casaroli-Marano, R.P.; Porta, O.; Vilarrodona, A.
Graphical abstract: Highlights: Acellular dermal matrix can be obtained with two days decellularization protocol. Biomechanical properties of split-thickness acellular dermal matrix are maintained when compared with native skin. DNA quantity in acellular dermal matrix is below 50 ng/mg dry tissue. Collagen and GAGs quantity are maintained after decellularization process, however elastin diminish. Abstract: Background: Dermal scaffolds for tissue regeneration are nowadays an effective alternative in not only wound healing surgeries but also breast reconstruction, abdominal wall reconstruction and tendon reinforcement. The present study describes the development of a decellularization protocol applied to human split-thickness skin from cadaveric donors to obtain dermal matrix using an easy and quick procedure. Methods: Complete split-thickness donor was decellularized through the combination of hypertonic and enzymatic methods. To evaluate the absence of epidermis and dermal cells, and ensure the integrity of the extracellular matrix (ECM) structure, histological analysis was performed. Residual genetic content and ECM biomolecules (collagen, elastin, and glycosaminoglycan) were quantified and tensile strength was tested to measure the effect of the decellularization technique on the mechanical properties of the tissue. Results: Biomolecules quantification, residual genetic content (below 50 ng/mg dry tissue) and histological structure assessment showed the efficacy of the decellularization process and the preservation of the ECM. The biomechanical tests confirmed the preservation of native properties in the acellular tissue. Conclusions: The acellular dermal matrix obtained from whole split-thickness skin donor with the newly developed decellualrization protocol, maintains the desired biomechanical and structural properties and represents a viable treatment option for patients.